Beyond Tax Knowledge: Exploring the Impact of Digital Literacy and Tax Stereotypes on MSME Tax Compliance (Case Study on MSME Taxpayers in Kesambi District, Cirebon, West Java, Indonesia) - Sholihah, Aminatus; Nugroho, Lucky (Business, Management & Accounting Journal (BISMA), 2025)
This study addresses the low level of tax compliance among MSMEs in Kesambi District, which remains a persistent issue despite existing tax policies. The phenomenon gap lies in the insufficient understanding of how tax literacy, digital literacy, and tax stereotypes influence compliance behavior. While previous studies have focused on individual aspects of tax compliance, limited research has examined the combined effect of these three variables. This research analyzes the impact of tax literacy, digital literacy, and tax stereotypes on MSME taxpayer compliance. A quantitative research method was employed, using primary data collected through structured questionnaires distributed to 125 MSME taxpayers. The data were analyzed using Partial Least Square (PLS) version 3.0, encompassing validity and reliability tests and structural model analysis. The results indicate that tax literacy does not significantly affect tax compliance, suggesting that mere knowledge of tax regulations is insufficient to drive compliance. Conversely, digital literacy significantly influences tax compliance, demonstrating the importance of digital access in facilitating tax reporting and payment. Additionally, tax stereotypes negatively impact compliance, highlighting the role of perceptions and trust in shaping taxpayer behavior. The findings provide theoretical implications by integrating the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) in tax compliance research. The study suggests improving digital literacy and addressing tax-related stereotypes can enhance voluntary tax compliance. This research contributes novelty by examining the interplay of these three factors, offering new insights for policymakers in designing more effective tax strategies.